Scabies‐induced perforating dermatosis successfully treated with low dose methotrexate - Elena Ippoliti; Niccolò Gori; Andrea Chiricozzi; Alessandro Di Stefani; Ketty Peris (Wiley, 2024)
Abstract We report the case of an 82‐year‐old diabetic patient, affected by a severe form of scabies‐induced acquired reactive perforating dermatosis, who was successfully treated with low‐dose methotrexate. Acquired reactive perforating dermatosis is a rare cutaneous disease, characterized by the extrusion of abnormal collagen through the epidermis and/or follicular units, mostly occurring in adult patients affected by systemic disorders, sharing itch as a symptom (e.g., diabetes, chronic kidney disease). The induction of acquired perforating dermatosis by scabies has been rarely reported in literature, and in almost all cases occurred in diabetic patients. Several lines of evidence suggest that skin traumatism induced by scratch could elicit perforating disorders in patients with diabetic dermal microangiopathy.